Ethanolic Extracts of Mulberry (Morus alba Linn) Leaf Prevent Hyperlipidemia and Oxidative Stress-induced Steatohepatitis in Rats - Sari, Wening (Universitas Muhammadiyah Surakarta, 2019)
Non Alcoholic steatohepatitis (NASH) is associated with the inflammation of fatty liver due to insulin resistance, dyslipidemia and oxidative stress. Treatment of NASH focused on control metabolic disorder and minimizes oxidative stress. White mulberry (Morus alba Linn) leaf has been reported for its anti-cholesterol and antioxidant effect. This study focused on effects of ethanolic extracts of white mulberry (EEM) leaf to total cholesterol, triglycerides and malondialdehyde (MDA) level of a high-fat diet induced steatohepatitis in rats.The experimental animals, male Wistar strain rats, divided into 5 groups. The rats fed high-fat diet to induced NASH and treated by 90, 180 and 360 mg/bodyweight/day of EEM for 21 successive days. The remaining 2 groups served as control, they fed standard and high-fat diet only. At the end of treatment all subjects were sacrificed using decapitation method. Blood was collected and measured for total cholesterol and triglycerides (Randox). Liver tissue was collected for MDA measurement and histopathologic preparation using haematoxylin-eosin staining. MDA level was measured using thiobarbituric acid reactive-substances (TBARS) method for oxidative stress measurement. EEM treatment significantly reduce cholesterol, triglycerides, and MDA levels as compared with high-fat diet control group (p<0.05). This result in line with histopathological finding as indicated by relatively mild hepatocytes cellular damage. It was conclude that EEM might prevent hyperlipidemia and oxidative stress-induced steatohepatitis.